Smectic-like bâtonnets in nematic/twist-bend nematic biphasic samples. Issue 1 (2nd January 2017) - Meyer, C.; Stoenescu, D.; Luckhurst, G. R.; Davidson, P.; Dozov, I.
ABSTRACT: We have studied a mixture of the twist-bend nemogenic dimer CB7CB with rod-like nematic molecules, which exhibits nematic (N) and twist-bend nematic (NTB ) phases and a very large biphasic coexistence range. At the N-NTB transition, we observe the nucleation of highly anisometric NTB droplets which are very similar to the classic smectic A (SmA) bâtonnets. These observations confirm the recently proposed close analogy between the NTB and SmA phases, on the basis of their identical macroscopic symmetry. As for their smectic analogues, the NTB bâtonnets are fluid in two dimensions; they easily merge when brought into contact and they are solid-like in that they did not flow along their optic axis. The observed fluidity and low viscosity show that the NTB phase is indeed a nematic phase, i.e. an anisotropic fluid, rather than a soft crystal or glassy state. Unlike their smectic analogues, the NTB bâtonnets have almost perfect symmetry of revolution and the axis of the NTB helix is uniformly aligned parallel to the long axis of the bâtonnet. The large aspect ratio of the bâtonnets, typically ≈ 10–30, indicates a very strong anisotropy of the N-NTB interfacial energy, W 2 / W 0  ≈ 200–2000, and suggests that the anchoring energy differs from the usual Rapini–Papoular form. GRAPHICAL ABSTRACT: